Weakly connected dominating set-based secure clustering and operation in distributed sensor networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (Inderscience Publishers, 2009)
This paper presents an efficient approach to secure network formation in distributed sensor networks (DSNs), which could be used for secure communications among the nodes after the start of the network’s operation. The structure of the network is formed on the basis of offline rank assignments by pre-distribution of secret keys to the participating sensors. Our approach uses the notion of weakly connected dominating set (WCDS) to reduce the number of cluster-heads in the network for greater resource efficiency. The clusters in the network are formed in a secure and efficient way so that no hostile entity could be included in any cluster during network structuring process. We propose an efficient algorithm to form a network-wide secure WCDS, which includes an optional re-keying mechanism to increase the level of security. Our objective is to ensure security in distributed sensor network from the bootstrapping stage up to the beginning of its operation. Along with the description of our approach, we present detailed analysis, simulation results and comparisons of our approach with other related schemes.